TEACHING SPEAKING THROUGH PICTURE SERIES - Putri Nur Azijah Mailani; Rida Farhana (PROJECT (Professional Journal of English Education), 2018)
The objective in this research was to find out whether or not  The use of Picture Series in Teaching Speaking was effective to improve the students’ speaking ability to in Junior High School. In this research the writer used one group pretest-posttest designs. The population of this research in FirstGrade class students of the Junior High School and the sample in First class. The instrument of this research was speaking test. The data of this research were collected by giving pretest and posttest.  Then, The collected data was calculated by using SPPS version 24. The result of this research show, that Normality distribution value of pretest 0.132 and significance values of posttest is 0.200 the data was normal because both of significance value more than 0.05,and significance value (2-tailed) of t-test lower than 0.05.  It mean the null hypothesis (Ho) is rejected.Thus, it can be concluded The use of picture series in teaching speaking  is effective in improving students speaking ability, it is similar to this research.Keywords:  Picture Series, Speaking Skill